Pathway‐Based Analysis of Microarray and RNAseq Data Using Pathway Processor 2.0. Issue 1 (1st March 2013) - Beltrame, Luca; Bianco, Luca; Fontana, Paolo; Cavalieri, Duccio
Abstract: The constant improvement of high‐throughput technologies has led to a great increase in generated data per single experiment. Pathway analysis is a widespread method to understand experimental results at the system level. Pathway Processor 2.0 is an upgrade over the original Pathway Processor program developed in 2002, extended to support more species, analysis methods, and RNAseq data in addition to microarrays through a simple Web‐based interface. The tool can perform two different types of analysis: the first covers the traditional Fisher's Test used by Pathway Processor and topology‐aware analyses, which take into account the propagation of changes over the whole structure of a pathway, and the second is a new pathway‐based method to investigate differences between phenotypes of interest. Common problems and troubleshooting are also discussed. Curr. Protoc. Bioinform . 41:7.6.1‐7.6.12. © 2013 by John Wiley & Sons, Inc.